Necrotising enterocolitis after supraventricular tachycardia: an unusual precursor to a common problem - Saini, Jennie (BMJ Case Rep, 2017)
Supraventricular tachycardia (SVT) is the most common neonatal arrhythmia. Necrotising enterocolitis (NEC) is a disease with multifactorial aetiology, most common in preterm infants. There are three previous case reports in the literature of NEC following neonatal SVT. We present two cases of late preterm infants with NEC, characterised by pneumatosis on abdominal X-ray and ultrasound, following recurrent SVT without haemodynamic instability. The infants were successfully treated with antibiotic therapy and bowel rest.